Alternative soilless media using olive-mill and paper waste for growing ornamental plants - Chrysargyris, Antonios; Antoniou, Omiros; Tzionis, Andreas; Prasad, Munoo; Tzortzakis, Nikos G. (My University, 2018)
Peat-based growing media are not ecologically sustainable and peat extraction threatens sensitive peatland ecosystem. In this study, olive-stone waste (OSW) and paper waste (PW) were used in different ratios—as growing media—for ornamental crop production, as peat (P) substitutes. Marigold (Calendula officinalis L.), petunia (Petunia x hybrita L.) and matthiola (Matthiola incana L.) plants were grown in (1) P (100%), (2) P:OSW (90%:10%), (3) P:OSW (70%:30%), and (4) P:OSW:PW (60%:20%:20%). The physicochemical properties of these substrates and the effects on plant growth were determined. The addition of 10–30% OSW into the substrate increased marigold height compared to plants grown in 100% peat. No differences in plant size, plant biomass (leaves and flowers), and dry matter content were found. Adding PW, in combination with OSW, maintained marigold height and total number of flowers produced to similar levels as in plants grown in 100% peat. In matthiola, adding 30% OSW into the substrate reduced plant size and fresh weight, but not plant height. No differences were observed when plants grew in lower OSW (i.e., 10%) content. Petunia’s height, its total number of flowers and flower earliness (flower opening) were increased in the presence of OSW compared to the plants grown in 100% peat. The addition of OSW did not affect petunia’s size and fresh weight among treatments. The addition of PW suppressed several plant growth-related parameters for both matthiola and petunia. The insertion of OSW did not change leaf chlorophyll content whereas the presence of PW decreased chlorophylls for marigold, petunia, and matthiola. Both OSW and PW altered the content of total phenolics and antioxidant capacity of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) in leaves and flowers for marigold and petunia. Both 30% OSW and PW increased antioxidative enzyme metabolism due to the increased damage index and lipid peroxidation observed in plants. Leaf N and P content decreased in PW-based media, while matthiola displayed visual phytotoxicity symptoms when PW was added into the substrate. The present work indicates that up to 30% of OSW can replace peat for marigold and petunia growing and only up to 10% of OSW for matthiola, while the addition of PW on top of OSW is not recommended, so further research is needed.
Keywords: Antioxidants; Earliness; Growth; Olive-mill waste; Ornamentals; Paper waste; Peat